Insulin resistance increases loss of antibody to hepatitis B surface antigen in nondiabetic healthy adults. Issue 11 (8th June 2016) - Joo, E.‐J.; Yeom, J.‐S.; Kwon, M.‐J.; Chang, Y.; Ryu, S.
Summary: The aim of this study was to evaluate the impact of insulin resistance on the persistence of a protective level of anti‐HBs (hepatitis B surface antigen) in a nondiabetic general population. A cohort study was designed comprising of 38 473 Korean men and women with anti‐HBs at concentrations ≥10 mIU/mL, who underwent a health examination. Insulin resistance was assessed with a homoeostasis model assessment of insulin resistance (HOMA‐IR). A decline in anti‐HBs to <10 mIU/L during the follow‐up was considered to be a loss of protective anti‐HBs. Cox‐proportional hazard models were used to estimate the adjusted hazard ratios and 95% confidence intervals for anti‐HBs loss across quintiles of HOMA‐IR and insulin. We identified 20 826 incidents of loss of anti‐HBs antibody during 180 522 person‐years of follow‐up (incident rate 11.5 per 100 person‐years). Increasing HOMA‐IR was positively associated with incident loss of anti‐HBs. The multivariable‐adjusted hazard ratios (95% confidence intervals) for incident loss of anti‐HBs comparing quintiles 2–5 vs quintile 1 of HOMA‐IR were 1.09 (1.04–1.14), 1.14 (1.09–1.19), 1.14 (1.09–1.19) and 1.21 (1.16–1.27), respectively. These associations were stronger in younger individuals under the age of 35 than in people 35 years of age or older ( P for interaction = 0.004). The association was also more evident in subjects with higher titres (≥100 mIU/mL) of anti‐HBs than in those with low titres ( P for interaction < 0.001). Insulin resistance was associated with an increased risk for loss of vaccine‐acquired anti‐HBs in a large sample of a nondiabetic, general population, indicating a possible role of insulin resistance in vaccine‐induced immunity.